POTENSI ANTHELMETIKA SERBUK BIJI ALPUKAT TERHADAP CACING Haemonchus contortus PADA TERNAK DOMBA SECARA IN VITRO (Potency of Avocado Seed Powder (Persea Americana Mill) Anthemintic on Haemonchus Contortus Worms Sheep In vitro) - Widiarso, Budi Purwo; Kusmawati, Anindita Aulia (Universitas Nusa Cendana, 2024)
Haemonchosis is a livestock health problem with a high prevalence in Indonesia which causes decreased production, anemia, huge economic losses and has fatal consequences for young sheep. The most common treatment and prevention of worms is the use of broad-spectrum chemical anthelmintics, but if used continuously it can result in resistance and residues to livestock products which are a serious threat to livestock production. This study aims to determine the effect of avocado seed powder (Persea americana Mill) on the mortality of Haemonchus contortus worms in sheep in vitro. This study used 5 treatments of Haemonchus contortus worms with 3 replications, consisting of P1 (Physiological NaCl) as a negative control, P2 (25% avocado seed powder), P3 (50% avocado seed powder), P4 (75% avocado seed powder). , and P5 (Albendazole) as positive control. Data were analyzed using One Way Annova analysis with SPSS 20. The results showed that avocado seed powder can be used as a natural anthelmintic with 100% worm mortality at a dose of 75% because contain tanin 6,40% w/w